2010
DOI: 10.1016/j.freeradbiomed.2009.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa thymoquinone-rich fraction greatly improves plasma antioxidant capacity and expression of antioxidant genes in hypercholesterolemic rats

Abstract: The antioxidant activities of the thymoquinone-rich fraction (TQRF) extracted from Nigella sativa and its bioactive compound, thymoquinone (TQ), in rats with induced hypercholesterolemia were investigated. Rats were fed a semipurified diet supplemented with 1% (w/w) cholesterol and were treated with TQRF and TQ at dosages ranging from 0.5 to 1.5 g/kg and 20 to 100 mg/kg body wt, respectively, for 8 weeks. The hydroxyl radical (OH(.))-scavenging activity of plasma samples collected from experimental rats was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
140
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(158 citation statements)
references
References 35 publications
14
140
0
4
Order By: Relevance
“…Moreover, the level of NO increased significantly in the frontal lobe of the NS and FA-treated group compared to FA-treated rats. This is in agreement with the study of Ismail et al [57] who reported that thymoquinone had an inhibitory effect on lipid peroxidation and markedly improved plasma antioxidant status by inhibiting formation of hydroxyl radicals.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the level of NO increased significantly in the frontal lobe of the NS and FA-treated group compared to FA-treated rats. This is in agreement with the study of Ismail et al [57] who reported that thymoquinone had an inhibitory effect on lipid peroxidation and markedly improved plasma antioxidant status by inhibiting formation of hydroxyl radicals.…”
Section: Discussionsupporting
confidence: 93%
“…The importance of the volatile oil fraction in the suppression of oxidation of its parent crude oil is attributed to its content of thymoquinone (TQ). This volatile compound is known to possess a potent antioxidant activity (Ismail et al, 2009). The results in Table 2 indicate that the thymoquinone (TQ) percentage of the volatile oil isolated from the SPO was higher (68.13%) than that isolated from the HPO (56.29%).…”
Section: Discussionmentioning
confidence: 99%
“…Other medical effects like: Antiasthmatic (M.H. Boskabady, et al 2010), protective toxicity (Ahmed M. Mohamadin et al 2010), plasma antioxidant capacity (Maznah Ismail et al 2010, Mahmoud et al, 2015, antifungal (Eugene A. Rogozhin et al 2010), anti-nephrotoxicity (İhsan and Engin 2010), antiallergic (Soheila et al 2010, retards the progression of atherosclerosis (Mohammad and Hedi, 2010) and many other diseases (G. Lupidi, et al 2010, Osama andSoliman, 2010) were cited.…”
Section: Introductionmentioning
confidence: 99%